R-Functions and WA-Systems of Functions in Modern Information Technologies - Kravchenko, Victor F.; Kravchenko, Oleg V.; Konovalov, Yaroslav Yu.; Pustovoit, Vladislav I.; Churikov, Dmitry V. (NTU "KhPI", 2016)
The review report consists of five parts. It describes the main physical applications of atomic, WA-systems and R-functions.
Keywords: atomic functions; R-functions; WA-systems of function; wavelets; DSP